2020
DOI: 10.1108/pijpsm-07-2019-0122
|View full text |Cite
|
Sign up to set email alerts
|

Reporting cybercrime victimization: determinants, motives, and previous experiences

Abstract: PurposeCybercrime rates have increased rapidly during the last couple of decades, resulting in cybercrimes becoming common crimes. However, most victims do not report cybercrimes to the police. Therefore, this study examines reporting cybercrime victimization and provides insights into the role of the police in this process.Design/methodology/approachA sample of 595 individuals was used. All respondents were shown three vignettes about hypothetical cybercrime victimization and were asked to imagine that this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
0
12
1
4
Order By: Relevance
“…Interestingly, only 13.1% of offenses were reported to the police, which is in line with the 12.5% report rate found in the current study. Although Van de Weijer et al (2020) also found that victims were more likely to report their victimization to other organizations than the police (33.2%), this effect was much larger in our study (87.5%). The low cybercrime occurrence in our study has methodological implications.…”
Section: Experience With Online Bankingcontrasting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, only 13.1% of offenses were reported to the police, which is in line with the 12.5% report rate found in the current study. Although Van de Weijer et al (2020) also found that victims were more likely to report their victimization to other organizations than the police (33.2%), this effect was much larger in our study (87.5%). The low cybercrime occurrence in our study has methodological implications.…”
Section: Experience With Online Bankingcontrasting
confidence: 82%
“…From a victim point of view, this decision to reach out to other organizations than the police is understandable. The majority of cybercrime victims have negative experiences with reporting their victimization to the police (Van de Weijer et al, 2020) and banks play a role both in the detection of anomalies to prevent cybercrime from happening and in incident handling once the crime has occurred. It is therefore not strange that banks have taken several measures to increase user compliance, including the implementation of several Information Security Awareness (ISA) programs (Bauer, Bernroider, & Chudzikowski, 2017) and recommendations for the security of Internet payments by the European Central Bank (ECB), 2013).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some experience no loss so don't bother to report. Some think it's unlikely the police will do anything to name some (see Button and Cross, 2017;Leukfeldt et al, 2020;van de Weijer et al, 2019;van de Weijer et al, 2020).…”
Section: Computer Virus Offencesmentioning
confidence: 99%
“…El reflejo de los ciberdelitos en las estadísticas oficiales podría estar afectado, en mayor medida que los delitos tradicionales, por factores relacionados con la infra-denuncia. Algunos estudios han mostrado que las cibervíctimas denuncian con menos frecuencia que las víctimas de delitos convencionales (Van de Weijer et al, 2020). El bajo índice de denuncia de los ciberdelitos puede verse afectado por diversos factores relacionados con el desconocimiento por parte de la víctima de su propia cibervictimización, la reticencia a denunciar por parte de la víctima debido a la poca gravedad de los hechos sufridos o a la desconfianza en la detección del autor.…”
Section: Limitaciones De Las Fuentes De Datos De La Ciberdelincuenciaunclassified